Pengaruh Media Sosial terhadap Pola Komunikasi Siswa kepada Guru - St. Rahmah; Samuel Hady Gandojo; Rahmi; Floren Olantara; Aat Ruchiat Nugraha; Muhammadong (EDU RESEARCH, 2023)
This research attempts to explore the impact of social media use on students' communication patterns with teachers in an educational context. In the increasingly advanced digital era, social media has become a significant element in changing the way humans interact and communicate. Communication between students and teachers is key in creating an effective learning experience. Teachers are not only conveyors of knowledge, but also guides, mentors and sources of inspiration for students. The quality of communication between students and teachers affects students' understanding, motivation and interactions that support the learning process. However, with the deepening use of social media by students, this communication pattern has undergone significant changes. This study uses a quantitative approach and quantitative descriptive research type. The measurement instrument used was a questionnaire with a Likert scale to explore students' views on social media and their communication patterns with teachers. The results of the analysis showed a significant influence between the use of social media and students' communication patterns with teachers, with social media contributing 70%. These results illustrate the importance of social media in supporting an effective learning process and emphasise the need for a deeper understanding of its impact.